Effects of humic acid on chlorophyll content and root length of ryegrass (lolium multiflorum lam.) - Jing He,; Yanan Li, (Bangladesh Journal of Botany, 2023)
Use of humic acid has great significance to improve soil quality and crop yield in loess hilly and gully areas. In the present study, potassium humate (PH) and potassium fulvic acid (PFA) were used as soil amendments in gully the control project area of Yan'an City, Shaanxi Province. A pot culture experiment was conducted to evaluate the influence of two types of humic acid (PH and PFA) on the growth characteristics of ryegrass in the loess hilly and gully area. Results showed that application of potassium humate and potassium fulvic acid considerably increased the chlorophyll synthesis as well as root length of ryegrass. When the proportion of PH and PFA was the same, the effect of PFA was to be found better than that of PFH. When the proportion of potassium humate was 15g/kg soil, the leaf chlorophyll content and root length attained the maximum, and the soil maturity effect was the best. Bangladesh J. Bot. 52(2): 467-472, 2023 (June) Special